Psychosocial working conditions and mental health among medical assistants in Germany: a scoping review - Kira Schmidt-Stiedenroth; Viola Mambrey; Annegret Dreher; Adrian Loerbroks (BMC Public Health, 2024)
Abstract Background Medical assistants (MA) constitute one of the largest professions in outpatient health care in Germany. The psychosocial working conditions of health care staff are generally believed to be challenging and to thereby increase the risk of poor mental health. A review of MA’s psychosocial working conditions and mental health is lacking, however. We aimed to systematically identify and summarize existing research on psychosocial working conditions and mental health of MA by addressing (1) Which methods, concepts, and instruments have been used to capture the psychosocial working conditions and mental health among MA in Germany? (2) What findings are available? and (3) What are the research gaps? Methods We systematically searched Medline, Scopus, CCMed and Google Scholar. Using the Population Concept Context (PCC)-framework, we applied the following eligibility criteria: (a) Language: English or German, (b) publication between 2002-2022, (c) original study, (d) study population: mainly MA (i.e., ≥ 50% of the study population), (e) concept: psychosocial working conditions and/or mental health, and (f) context: Germany. Two reviewers extracted data independently, results were compared for accuracy and completeness. Results Eight hundred twenty-seven sources were identified. We included 30 publications (19 quantitative, 10 qualitative, and one mixed methods study). Quantitative studies consistently reported high job satisfaction among MA. Quantitative and mixed methods studies frequently reported aspects related to job control as favorable working conditions, and aspects related to job rewards as moderate to unfavorable. Qualitative studies reported low job control in specific work areas, high demands in terms of workload, time pressure and job intensity, and a desire for greater recognition. Social interactions seemed to be important resources for MA. Few studies (n = 8) captured mental health, these reported inconspicuous mean values but high prevalences of anxiety, burnout, depression, and stress among MA. Studies suggested poorer psychosocial working conditions and mental health among MA during the COVID-19 pandemic. Conclusions Quantitative studies tend to suggest more favorable psychosocial working conditions among MA than qualitative studies. We suggest mixed methods to reconcile this alleged inconsistency. Future research should examine discrepancies between job satisfaction and unfavorable working conditions and if psychosocial working conditions and mental health remain changed after the COVID-19 pandemic.